Composition of outer-sphere cations as a tool for electrochemical synthesis of novel niobium compounds - Grinevitch V.V.; Arakcheeva A.V.; Kuznetsov S.A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The individual alkali-metal cation influence on the chemical and phase composition of electrosynthesis products has been studied in fluoride solvents with different O/Nb ratios. It was shown that the cation nature of molten electrolytes is a powerful tool to control the chemical and phase composition of the cathodic products of electrolysis in oxy-fluoride and fluoride melts. New niobium compounds were obtained by electrochemical synthesis using the outer-sphere cations composition control: tetragonal Nb6O, rhombohedral sub-oxide NbxO (x<6) and composite compounds "NbO" ⋅n"MeF" (Me=K, Rb, n=1, 2).